UNFORESEEN DEVELOPMENT AS A DEVICE TO ASSESS SAFEGUARD INVESTIGATION - Wardana, Achmad Ferry Kusuma (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
Unforeseen Development requirement is indeed essential for the World Trade Organization (WTO) member countries to make safeguard investigations in their own country, this study has analysed the affecting unforeseen development requirement in safeguard investigations. Additionally, this study examined how an unforeseen development affects safeguard investigations in Indonesia. The method of this study is qualitative research, and descriptive research is to analyze the data by using case analyses. The author presents major findings by subject on unforeseen development covers increased imports, the stages of an investigation, and determination of safeguard measures. The results further confirm that this study shows policy implications to elaborate the effect of unforeseen developments for safeguard investigations and after a measure taken. Also, this study shows policy recommendations as added value on this study to improving standard quality. For addition, this study provides a new theory that calls three fresh arguments (Zhou and Fang 2022). The reader would be get the fruitful discussions and recommendations on safeguard basis especially to the unforeseen developments requirements under safeguard investigations.